Can AMPK mediated suppression of mTORC1 explain the concurrent training effect? - Hamilton, D. L.; Philp, A. (Cellular and Molecular Exercise Physiology, 2013)
Endurance and resistance exercise are divergent modes of exercise training which each drive mode specific adaptive responses. Some of these adaptations are mutually exclusive, whilst others drive divergent effects on muscle contractile properties, mass and metabolic function. When both resistance and endurance exercise training are employed together, a process termed `concurrent training`, there appears to be a reduction in skeletal muscle adaptive potential. In real world terms this is evident in decathletes, in which personal bests represent approximately a 25% reduction compared to competitors from individual events. This review will detail the molecular pathways thought to drive the resistance and endurance training response and discuss recent evidence addressing the cross talk between these molecular pathways. Ultimately we will address whether interference at the molecular level can in some part explain the repression on strength gains observed following concurrent training.